VTP Hayashi’: New cultivar of the Prata subgroup - Nomura, Edson Shigueaki; Damatto Junior, Erval Rafae; Fuzitani, Eduardo Jun; Godoi Farias, Guilherme Bueno de [UNESP] (FapUNIFESP (SciELO), 2024)
The aim of this study was to describe the main characteristics of development, production, and postharvest of the new cultivar of the Prata subgroup, ‘VTP Hayashi’, that is a natural mutation originating from ‘SCS451 Catarina’. The plants of VTP Hayashi showed greater height and diameter of the pseudostem and the fruits are longer, heavier, and more uniform in the cluster, characteristics that differ from ‘SCS451 Catarina’. The development and production cycles and the susceptibility to fungal diseases resemble those of ‘SCS451 Catarina’. At maturity stage 6, it presented average contents of soluble solids of 28.2ºBrix and titratable acidity of 0.69% of malic acid, higher than ‘SCS451 Catarina’. The selection of this cultivar was due to the position of the inflorescence in the vertical direction, giving it a better fruit development.
‘VTP Hayashi’: Nova cultivar do subgrupo Prata
Keywords: genetic improvement; Musa spp; production